2019
DOI: 10.18592/jsi.v7i2.3084
|View full text |Cite
|
Sign up to set email alerts
|

Adversity Quotient (AQ) dan Stres Kerja Pegawai Bagian Protokol Pemerintah Provinsi Jambi

Abstract: A precedence employee works not only in the office but also in the field. Fieldwork sometimes makes scheduled jobs changed at any time. This happens when a government leader visits the office. In that case, the precedence officer is obliged to facilitate all the attending guests to the event. This condition requires precedence employees to be available 24 hours a day. The number of jobs that must be completed in a short time can cause work stress on precedence employees. There are several ways to reduce work s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Several previous research results found that Adversity Quotient has a positive relationship with aspects of healthy behavior in students (Choompunuch, Suksatan, Sonsroem, Kutawan, & In-Udom, 2021);(Suksatan, Choompunuch, Koontalay, Posai, & Abusafia, 2021) with one of the indicators located in a person's ability to reduce the level of their stress faces (Kurniawan & Krisnawati, 2019). The potential Adversity Quotient also plays a role in an individual's strength in facing the challenges of the situation (Dorji & Singh, 2019).…”
Section: Potential Adversity Quotient In the Studentsmentioning
confidence: 95%
“…Several previous research results found that Adversity Quotient has a positive relationship with aspects of healthy behavior in students (Choompunuch, Suksatan, Sonsroem, Kutawan, & In-Udom, 2021);(Suksatan, Choompunuch, Koontalay, Posai, & Abusafia, 2021) with one of the indicators located in a person's ability to reduce the level of their stress faces (Kurniawan & Krisnawati, 2019). The potential Adversity Quotient also plays a role in an individual's strength in facing the challenges of the situation (Dorji & Singh, 2019).…”
Section: Potential Adversity Quotient In the Studentsmentioning
confidence: 95%